Relationships among loneliness, emotion dysregulation, sleep quality, and health-related quality of life in coronary heart disease patients - Choo, Rozenne Wei Kim (2018)
Cardiovascular disease is a principal cause of death in Singapore. Most of these deaths are due to coronary heart disease (CHD). Past studies have found a host of psychosocial risk factors predicting low levels of health-related quality of life (HRQoL) in CHD patients. Loneliness is prevalent in CHD patients, but it remains poorly understood as a predictor of low levels of physical HRQoL. Little is known if the relationship between loneliness and physical HRQoL may be moderated (i.e., exacerbated) by emotion dysregulation, and mediated by poor sleep quality. This study examined these potential relationships. Questionnaires on loneliness, emotion dysregulation, sleep quality, and physical HRQoL were administered to 208 participants from a cardiac rehabilitation programme in Singapore. Hierarchical regression analyses were conducted to test the potential relationships. Results indicated that higher levels of loneliness predicted lower levels of physical HRQoL. This relationship was not moderated by emotion dysregulation. However, poor sleep quality partially mediated this relationship. Findings suggested that CHD patients who were lonely could suffer from poor sleep quality and, eventually, low levels of physical HRQoL. Further analyses revealed that two components of sleep quality, sleep latency and daytime dysfunction, contributed to its partial mediation effect. In other words, CHD patients who were lonely appeared to have low levels of physical HRQoL partially through poor sleep quality, specifically prolonged sleep latency and more daytime dysfunction. It is recommended for healthcare professionals to assess and address loneliness and poor sleep quality in CHD patients to enhance their physical HRQoL.